2020
DOI: 10.1037/tra0000648
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neurofeedback training on children with developmental trauma: A randomized controlled study.

Abstract: Objective: Developmental trauma or chronic early childhood exposure to abuse and neglect by caregivers has been shown to have a long-lasting pervasive impact on mental and neural development, including problems with attention, impulse control, self-regulation, and executive functioning. Its long-term effects are arguably the costliest public health challenge in the United States. Children with developmental trauma rarely have a satisfactory response to currently available evidence-based psychotherapeutic and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 63 publications
5
55
0
1
Order By: Relevance
“…In this preliminary investigation, we report that alpha-rhythm EEG-NFB led to reductions on PTSD severity scores as well as increased rates of PTSD remission for the experimental NFB group. Our data qualitatively replicate previous clinical trials of EEG-NFB in patients with PTSD ( van der Kolk et al, 2016 , Rogel et al, 2020 ) and extend the mechanistic insights from our previous neuroimaging studies investigating a single session of alpha desynchronizing EEG-NFB ( Ros et al, 2013 , Kluetsch et al, 2014 ). Critically, aberrant DMN and SN connectivity patterns detected among PTSD patients at baseline (compared to healthy controls) in the current trial were found to shift towards normalization after active NFB treatment.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In this preliminary investigation, we report that alpha-rhythm EEG-NFB led to reductions on PTSD severity scores as well as increased rates of PTSD remission for the experimental NFB group. Our data qualitatively replicate previous clinical trials of EEG-NFB in patients with PTSD ( van der Kolk et al, 2016 , Rogel et al, 2020 ) and extend the mechanistic insights from our previous neuroimaging studies investigating a single session of alpha desynchronizing EEG-NFB ( Ros et al, 2013 , Kluetsch et al, 2014 ). Critically, aberrant DMN and SN connectivity patterns detected among PTSD patients at baseline (compared to healthy controls) in the current trial were found to shift towards normalization after active NFB treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, dropout rates from psychological therapies in PTSD remain a critical barrier to recovery ( Bisson et al, 2013 , Goetter et al, 2015 , Lewis et al, 2020 ). Finally, our EEG-NFB trial remission rates (61.1%) are comparable to those of current, gold standard treatments for PTSD ( Bradley et al, 2005 , Ehring et al, 2014 , van der Kolk et al, 2016 , Rogel et al, 2020 ). Taken together, NFB may represent a valuable adjunctive treatment for PTSD, where it has been suggested previously that NFB may be especially beneficial for PTSD patients experiencing high levels of anxiety, dissociation, and emotion dysregulation related to less optimal response to other forms of trauma-focused therapy ( van der Kolk et al, 2016 , Rogel et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations